The etiopathogenesis of uterine leiomyomas: A review - Ola M. Alali; Mikhail I. Churnosov (IP Berlin A.V., 2023)
Background. The most frequent female reproductive system tumors are uterine leiomyoma (UL). They are benign monoclonal tumors of uterine smooth muscle. They affect reproductive-age women with a lifetime prevalence of 3070%. UL is a disease with complex etiology determined by many genetic and environmental factors. Despite the frequency of UL, there is no long-term, cost-effective or fertility-preserving therapy option for it. Aim. To summarize the available literature data on the etiopathogenesis of uterine fibroids as well as the risk factors for the development of this disease. Materials and methods. The PubMed, Scopus, and Web of science literature databases were searched for relevant articles using such keywords as uterine fibroids, UL, association, genetic and hormonal factors, gene, etiology in various combinations. Results. Genetic disorders and hormonal and growth factors all have a part in the etiology of UL, and studies have resulted to the use of hormone therapy for fibroids, with varying results. Recent findings on the etiopathogenesis of UL, as well as the introduction of relevant genetically modified mouse models of UL, have rekindled interest in the disease. In this review, the basic features of fibroids are discussed, as well as the primary contributors to UL etiopathogenesis, including as genetic, hormonal, and growth causes. Besides the risk factors that contribute to the development of UL. Conclusion. Many questions about the causes and mechanisms of development factors that predispose remain unanswered, necessitating the continuation of these studies in order to obtain new information. Prospective studies are needed to better understand the biology and epidemiological associations, both to better understand modifiable risk factors and to shed light on the etiopathogenesis of this disease.